Description of new chiactine-bearing sponges provides insights into the higher classification of Calcaronea (Porifera: Calcarea) - Alvizu, Adriana; Xavier, Joana R.; Rapp, Hans Tore (Zootaxa, 2019)
A recent phylogenetic study revealed a close relationship between chiactine-bearing (family Achramorphidae, order Leucosolenida) and pugiole-bearing (order Baerida) calcaronean sponges as well as new putative taxa within Achramorphidae. In this study, we present a revision of chiactine-bearing sponges based on morphological re-examination of type material and recently collected specimens, in addition to new molecular data for the ribosomal 18S and C-region of the 28S. We provide re-descriptions for all known chiactine-bearing species, and further describe two new species from the Antarctic (Achramorpha antarctica sp. nov. and Megapogon schiaparellii sp. nov.) and two new species and a new genus from the Nordic Seas (Achramorpha ingolfi sp. nov. and Sarsinella karasikensis gen. nov. sp. nov.). The new phylogenetic reconstruction based on ribosomal 18S and C-region of the 28S confirms previous findings about the close relationship of some members of Baerida and the family Achramorphidae of the order Leucosolenida. However, new material and the addition of molecular data from the type species of both taxa would be required to formally propose changes at (sub-)ordinal levels within the classification of Calcaronean sponges.